2021
DOI: 10.1002/cam4.4386
|View full text |Cite
|
Sign up to set email alerts
|

Nonnegative matrix factorization‐based bioinformatics analysis reveals that TPX2 and SELENBP1 are two predictors of the inner sub‐consensuses of lung adenocarcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Our and previous results suggest that non-negative matrix factorization (NMF) is a robust clustering method in colon cancer 27 , 28 , liver cancer 29 , lung cancer 30 and lower grade glioma 31 . Here, using NMF algorithm, VHL mutant ccRCC from TCGA 7 and E-MTAB-1980 32 datasets was divided into two sub-clusters.…”
Section: Introductionmentioning
confidence: 64%
“…Our and previous results suggest that non-negative matrix factorization (NMF) is a robust clustering method in colon cancer 27 , 28 , liver cancer 29 , lung cancer 30 and lower grade glioma 31 . Here, using NMF algorithm, VHL mutant ccRCC from TCGA 7 and E-MTAB-1980 32 datasets was divided into two sub-clusters.…”
Section: Introductionmentioning
confidence: 64%
“…TPX2 is a spindle assembly factor required for the normal assembly of mitotic spindles, and TPX2 is frequently reported to be considerably increased in various cancers 52–54 . Elevated TPX2 expression shows a positive correlation with tumor grade, stage, lymph node metastasis, recurrence, and poor patient survival 53,55 . The TPX2/Aurora A kinase heterodimer complex orchestrates mitotic spindle events to maintain genome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Elevated TPX2 expression shows a positive correlation with tumor grade, stage, lymph node metastasis, recurrence, and poor patient survival. 53,55 The TPX2/Aurora A kinase heterodimer complex orchestrates mitotic spindle events to maintain genome integrity. Moreover, it counteracts 53BP1 chromatin accumulation to ensure genomic stability.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It has been suggested that TPX2 could be used as a marker for poor prognosis in lung adenocarcinoma (LUAD) by data analysis. [15][16][17] TPX2 overexpression also caused resistance to EGFR TKI and radiation in NSCLC. 18 So, understanding the mechanism of TPX2 has become an important issue.…”
Section: Introductionmentioning
confidence: 99%